A Literature Review on Collaborative Problem Solving for College and Workforce Readiness. Issue 1 (17th April 2017) - Oliveri, María Elena; Lawless, René; Molloy, Hillary
Abstract: The literature and the employee and workforce surveys rank collaborative problem solving (CPS) among the top 5 most critical skills necessary for success in college and the workforce. This paper provides a review of the literature on CPS and related terms, including a discussion of their definitions, importance to higher education and workforce success, and considerations relevant to their assessment. The goal is to discuss progress on CPS to date and help generate future research on CPS in relation to educational and workforce success. Abstract : Report Number: ETS RR‐17–06